2015
DOI: 10.7287/peerj.preprints.1145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The e-examination ecosystem in healthcare education: Information and process models

Abstract: Background: High stake assessments are an important component in all stages of healthcare education that validate learners’ clinical performance but may also inform and promote the learning process. Informatics has been a driver to transform paper examinations to digital examinations (e-examinations) but knowledge about their efficient and effective application in the context of healthcare assessment is still limited. Objective: The aim of this study is therefore to investigate the main aspects of the examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These tensions extend to the various technologies becoming available for e-examinations. Wholly online methods contend with secured word-processing applications for legal and medical assessments (Alfredsson, Sejersen, Stathakarou, & Zary, 2015;Chatzigavriil & Fernando, 2015;Poutre, Hedlund, & Nau, 2015). These studies have reported differences in candidate acceptance and perceptions of assessment validity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These tensions extend to the various technologies becoming available for e-examinations. Wholly online methods contend with secured word-processing applications for legal and medical assessments (Alfredsson, Sejersen, Stathakarou, & Zary, 2015;Chatzigavriil & Fernando, 2015;Poutre, Hedlund, & Nau, 2015). These studies have reported differences in candidate acceptance and perceptions of assessment validity.…”
Section: Literature Reviewmentioning
confidence: 99%